Serum organochlorines and non-Hodgkin lymphoma: A case-control study in Israeli Jews and Palestinians - Klil-Drori, Adi J.; Kleinstern, Geffen; Abu Seir, Rania; Choshen-Cohen, Lotan; Abdeen, Ziad; Hussein, Elyan; Aqel, Mohammad; Göen, Thomas; Perlman, Riki; Ben-Yehuda, Dina; Paltiel, Ora (Chemosphere, 2018)
Associations of organochlorine (OC) pesticides and polychlorinated biphenyls (PCBs) with non-Hodgkin lymphoma are controversial. We compared serum levels of 6 OC pesticides and 38 PCBs in Israeli Jews (IJ) and Palestinian Arabs (PA) and assessed possible associations with B-cell non-Hodgkin lymphoma (B-NHL). Ninety B-NHL cases (50 IJ and 40 PA) and 120 controls (65 IJ and 55 PA) were included. Median concentrations of analytes in controls were compared across ethnic groups using quantile regression, adjusting for age and sex. We used logistic regression to derive odds ratios (OR) and 95% confidence intervals (CI) for detectable analytes and B-NHL, adjusting for age, ethnic group, faming and body mass index. Median values of PCBs and dichlorodiphenyldichloroethylene (DDE) were higher in IJ vs PA controls (P = 0.0007), as were several PCBs (74, 99, 118, 138, 146, 153, 156, 163, 170, and 180). Overall, OC pesticide and PCB exposures were comparable with reports from high-income countries. B-NHL was associated with PCB 146 (OR 1.70, 95% CI: 1.02, 2.83), PCB 156 (OR 1.75, 95% CI: 1.06, 2.89), and high-chlorinated PCBs (OR 1.55, 95% CI: 1.00, 2.40) in all study subjects. These associations were robust in quantile as well as sensitivity analyses. An association of DDE with B-NHL was noted in PA (OR 1.72, 95% CI: 1.07, 2.77), but not in IJ (OR 0.87, 95% CI: 0.59, 1.27). Although high-chlorinated PCB concentrations did not indicate high exposure levels, our findings indicate that B-NHL may be associated with this exposure.
EVALuna2:35251